Kaizen and Implementation Suggestion in the Defense Industry: A Literature Review - Rusdiana, I Wayan; Soediantono, Dwi (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this article is to explore the benefits of implementing Kaizen in various industries and provide suggestions for application to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 30 international journal articles about the implementation of Kaizen published from 2014 to 2021 regarding the application of the Kaizen method in various industrial sectors and the defense industry. The analysis used used 25 content analysis of journal articles. The results of the literature review analysis state that the application of Kaizen can have benefits for companies, namely being able to avoid waste, being able to change and adapt quickly, produce products on time, complete products faster, improve production flow, improve product quality, develop responsive employees, help deal with uncertainty, increased productivity, reduced costs, improved quality, optimal use of resources, improved better communication, increased employee morale.